Järnberikning av mjöl : exemplifierat med Egypten och Iran - Johansson, Matilda (SLU/Dept. of Food Science, 2010)
The purpose of this study is to give an overview about iron fortification from the view of technique and health. Example of a technical aspect is different iron compounds which are used for fortification like ferrous sulfate, ferrous fumarate and elemental iron. In the aspect of health the big question is if iron fortification can improve the health in reducing the prevalence of anemia. The study focuses on flour fortification with iron in Egypt and Iran and involves a literature study with scientific articles. Also information from WHO (World Health Organization), FAO (Food and Agriculture Organization) and FFI (Flour Fortification Initiative) are used.